Evaluation of compressive strength and microhardness of composites associated to light curing characterizing materials - Barcellos, Daphne Câmara [UNESP]; Batista, Graziela Robeiro [UNESP]; Pleffken, Patrícia Rondon [UNESP]; Valera, Márcia Carneiro [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; de Araújo, Maria Amélia Máximo [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Aim: This study evaluated the microhardness and compressive strength of composite and light curing characterizing materials (LCCMs) by intrinsic technique. Materials and methods: Eighty composite specimens with a cylindrical shape were prepared and divided into eight groups (n = 10): Group E-composite-Enamel shade (ES); Group T- composite-Translucent shade (TS); Group W-White Tetric Color Pigment (Ivoclar/Vivadent) LCCM; Group B-Black Tetric Color Pigment (Ivoclar/Vivadent) LCCM; Group E/W/E-TS/ White Tetric Color Pigment LCCM/ES; Group E/B/E-ES/ Black Tetric Color Pigment LCCM/ES; Group E/W/T-ES/White Tetric Color Pigment LCCM/TS; Group E/B/T-ES/Black Tetric Color Pigment LCCM/TS. The specimens were submitted to a microhardness and compressive strength tests. Data were subjected to ANOVA, Tukey tests (5%) and pearson correlation. Results and conclusion: There were significant differences among the groups (p = 0.00). The Pearson correlation showed a p = 0.85. The mean values for microhardness: Group E-73.30a; Group T-66.47b; Group E/W/T-63.71bc; Group E/W/E-62.08bc; Group E/B/E-57.47c; Group E/B/T-55.61c; Group W-39.69d; Group B-37.87d. The mean values for compressive strength: Group E-493.12a; Group T-481.96a; Group E/B/E-359.45b; Group E/W/T-358.64b; Group E/B/T- 357.01b; Group E/W/E-353.73b; Group W-136.62c; Group B-41.22d. The use of LCCM by intrinsic technique reduced the microhardness and compressive strength of composite. There is a strong correlation between microhardness and compressive strength. Clinical significance: The use of light curing characterizing materials combined with direct resin restorations can adversely reduce microhardness and compressive strength of direct esthetic restorations.
Keywords: Composite; Compressive strength; Light curing characterizing materials; Microhardness